2018
DOI: 10.1021/acs.est.8b02301
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Polyethylene and Plastic Mixtures in Mealworms (Larvae ofTenebrio molitor) and Effects on the Gut Microbiome

Abstract: Recent studies have demonstrated the ability for polystyrene (PS) degradation within the gut of mealworms ( Tenebrio molitor). To determine whether plastics may be broadly susceptible to biodegradation within mealworms, we evaluated the fate of polyethylene (PE) and mixtures (PE + PS). We find that PE biodegrades at comparable rates to PS. Mass balances indicate conversion of up 49.0 ± 1.4% of the ingested PE into a putative gas fraction (CO). The molecular weights ( M) of egested polymer residues decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
312
3
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(355 citation statements)
references
References 28 publications
(95 reference statements)
25
312
3
15
Order By: Relevance
“…However, polymers with greater crystallinity, such as polyethylene, may be more resistant. Nonetheless, Brandon et al () observed similar rates of degradation of polyethylene and polystyrene by mealworms and that this was facilitated by adaption of their microbiomes. Microbial growth during use is a concern in a number of plastic applications, such as kitchenware.…”
Section: The Nature Of Plastics and Microplasticsmentioning
confidence: 99%
“…However, polymers with greater crystallinity, such as polyethylene, may be more resistant. Nonetheless, Brandon et al () observed similar rates of degradation of polyethylene and polystyrene by mealworms and that this was facilitated by adaption of their microbiomes. Microbial growth during use is a concern in a number of plastic applications, such as kitchenware.…”
Section: The Nature Of Plastics and Microplasticsmentioning
confidence: 99%
“…Marine bacteria are potential candidates for use in the biodegradation of plastic wastes [150]. PS is known to biodegrade in the gut of yellow mealworms [151]. Many fungal strains can also degrade several plastics, such as PVC, PHB, and PLA [39].…”
Section: Solutions For Reducing Plastic Micromaterials and Nanomaterialsmentioning
confidence: 99%
“…This finding was replicated with T. molitor populations from several regions of the world (Yang, Chen, et al, ) as well as its congener T. obscurus (Peng et al, ). T. molitor was also found to be able to biodegrade polyethylene in much the same manner (Brandon et al, ). Kundungal et al () fed polyethylene film alone or with beeswax to larvae of the lesser wax moth Achroia grisella and observed partial biodegradation, with some of the plastic excreted in faeces.…”
Section: Microbes and Fauna: Increased Palatability And Further Fragmmentioning
confidence: 88%